Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481345
|View full text |Cite
|
Sign up to set email alerts
|

Validating a mobile phone application for the everyday, unobtrusive, objective measurement of sleep

Abstract: There is an identified need for objective, reliable, and scalable methods of measuring and recording sleep. Such methods must be designed for easy integration into people's lives in order to support both sleep therapy and everyday personal informatics. This paper describes the design and evaluation of a mobile phone application to record sleep, the design of which has substantive foundation in clinical sleep research. Two user studies were carried out which demonstrate that the application produces valid measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…We also found features in mobile phone usage, wearable sensor and survey data that were significantly related to perceived stress level using correlation analysis. In the current study, we have increased our sampling period to ~30-days per person and our population to 66 participants to collect more intensive multi-modal data including perceived stress, sleep, personality, physiological, behavioral and social interaction data that are important factors in academic performance, sleep, stress, and mental health in addition to what were monitored on the phone in previous studies [4, 5, 8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…We also found features in mobile phone usage, wearable sensor and survey data that were significantly related to perceived stress level using correlation analysis. In the current study, we have increased our sampling period to ~30-days per person and our population to 66 participants to collect more intensive multi-modal data including perceived stress, sleep, personality, physiological, behavioral and social interaction data that are important factors in academic performance, sleep, stress, and mental health in addition to what were monitored on the phone in previous studies [4, 5, 8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Their results revealed that external stimuli would affect sleep quality, even though the stimuli was applied before sleeping. Lawson et al [7] explored if mobile phone application can be used to influence sleep. They produced short 4-second low frequency (95Hz) low volume tone every 15 minutes to observe people's sleep condition changes.…”
Section: Stimuli Interventionmentioning
confidence: 99%
“…For sleep quality evaluation and diagnosis, a subject's polysomnogram (PSG) recordings, which include an electroencephalogram (EEG), an electrooculogram (EOG) and an electromyogram (EMG), are usually measured and scored by an expert, who then classifies each 30-s epoch into one of the following sleep stages: wakefulness (Wake), non-REM sleep (Stages 1-4) and REM sleep (REM). The Wake stage consists of alpha activity (8)(9)(10)(11)(12)(13) or low-voltage mixed frequency activity. Stage S1 consists of related low-voltage mixed activity (3)(4)(5)(6)(7); Stage S2 is of the appearance of sleep spindles and/or K-complexes.…”
mentioning
confidence: 99%
“…Several activity-based methods [6], [7], wearable devices [8]- [10] or mobile applications [11], have been proposed to monitor sleep efficiency (wake-sleep states) using accelerometers to detect body movements during sleep. These devices are easy to use but might not support accurate recognition of the five sleep stages or real-time sleep-stage analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation